Synaptic AP2 CCV life cycle regulation by the Eps15, ITSN1, Sgip1/AP2, synaptojanin1 interactome - R. Mishra (Nature Portfolio, 2021)
Abstract The AP1/σ1B knockout causes impaired synaptic vesicle recycling and enhanced protein sorting into endosomes, leading to severe intellectual disability. These disturbances in synaptic protein sorting induce as a secondary phenotype the upregulation of AP2 CCV mediated endocytosis. Synapses contain canonical AP2 CCV and AP2 CCV with a more stable coat and thus extended life time. In AP1/σ1B knockout synapses, pool sizes of both CCV classes are doubled. Additionally, stable CCV of the knockout are more stabilised than stable wt CCV. One mechanism responsible for enhanced CCV stabilisation is the reduction of synaptojanin1 CCV levels, the PI-4,5-P2 phosphatase essential for AP2 membrane dissociation. To identify mechanisms regulating synaptojanin1 recruitment, we compared synaptojanin1 CCV protein interactome levels and CCV protein interactions between both CCV classes from wt and knockout mice. We show that ITSN1 determines synaptojanin1 CCV levels. Sgip1/AP2 excess hinders synaptojanin1 binding to ITSN1, further lowering its levels. ITSN1 levels are determined by Eps15, not Eps15L1. In addition, the data reveal that reduced amounts of pacsin1 can be counter balanced by its enhanced activation. These data exemplify the complexity of CCV life cycle regulation and indicate how cargo proteins determine the life cycle of their CCV.